2022
DOI: 10.3390/ijerph19127319
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopment in Normocephalic Children Exposed to Zika Virus in Utero with No Observable Defects at Birth: A Systematic Review with Meta-Analysis

Abstract: Zika virus (ZIKV) infection during pregnancy is a cause of pregnancy loss and multiple clinical and neurological anomalies in children. This systematic review aimed to assess the effect of ZIKV exposure in utero on the long-term neurodevelopment of normocephalic children born to women with ZIKV infection in pregnancy. This review was conducted according to the PRISMA guidelines for systematic reviews and meta-analyses. We performed a random effects meta-analysis to estimate the cross-study prevalence of neurod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 41 publications
0
11
0
1
Order By: Relevance
“…To characterize the sensitivity of human astrocytes to ZIKV infection during different developmental periods, we used pure astrocytes cultures or mixed cultures of human neurons and astrocytes obtained at different developmental stages to determine their infectivity and viral replication. Figure 1 represents a time course summary of ZIKV congenital syndrome as described [ 4 , 29 , 45 , 53 ]. We denote the timeline of gestation (arrows), neurogenesis, astrogenesis, growth and differentiation, and the correlation of these neurodevelopmental stages with ZIKV infection and brain abnormalities detected by ultrasound and our studies between 16 and 22 weeks post-conception, wpc ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To characterize the sensitivity of human astrocytes to ZIKV infection during different developmental periods, we used pure astrocytes cultures or mixed cultures of human neurons and astrocytes obtained at different developmental stages to determine their infectivity and viral replication. Figure 1 represents a time course summary of ZIKV congenital syndrome as described [ 4 , 29 , 45 , 53 ]. We denote the timeline of gestation (arrows), neurogenesis, astrogenesis, growth and differentiation, and the correlation of these neurodevelopmental stages with ZIKV infection and brain abnormalities detected by ultrasound and our studies between 16 and 22 weeks post-conception, wpc ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Zika virus (ZIKV) was declared a Public Health Emergency by the World Health Organization (W.H.O.) from February 2016 to March 2017 [ 1 , 2 ]; however, the emergence of new viruses such as SARS-CoV-2 has reduced the interest in ZIKV despite its devastating consequences during developmental stages [ 3 ], [ 4 ], [ 5 ], [ 6 ], [ 7 ]. Despite the multiple outbreaks and epidemic proportions of ZIKV worldwide, the mechanism by which this virus compromises the developing brain only recently has been explored [ 8 ], [ 9 ], [ 10 ], [ 11 ], [ 12 ], [ 13 ], [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, it seems likely that at least those opossums with severe brain pathologies would exhibit abnormalities in behavior, social interactions, cognitive abilities, and memory if they were allowed to develop and were rigorously assessed. Recently, it has been demonstrated that some children who were exposed in utero to ZIKV and were not born with CZS exhibit delayed neurodevelopment and neurosensory alterations by the second year of life [ 42 ], and that some may have altered “executive function, mood, and adaptive mobility” by ages 3–5 years [ 43 ]. As a practical, non-genetically modified animal model that has a relatively short lifespan and can be utilized in large numbers, the opossum may prove to be critical for research on the long-term effects of in utero ZIKV infection on childhood development and into adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…A study of 70 Colombian infants with confirmed exposure to ZIKV during the pregnancy without CZS, assessed using the Warner Initial Developmental Evaluation of Adaptive and Functional Skills (WIDEA) up to 18 months found that there was a progressive deviation from normative levels on the WIDEA total, mobility, communication, and social cognition scores over time [75 ▪ ]. Meta-analysis of neurodevelopment in normocephalic children with prenatal ZIKV exposure found cognitive, language, or motor delay on Bayley-III in 6.5, 29.7, and 11.5% of children, respectively [76 ▪▪ ]. Reports of outcomes at older ages are beginning to appear.…”
Section: Neurological and Developmental Outcomes Of Congenital Infect...mentioning
confidence: 99%